1997
DOI: 10.1002/(sici)1096-9896(199707)182:3<266::aid-path812>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Quality assessment by expert opinion in melanoma pathology: experience of the Pathology Panel of the Dutch Melanoma Working Party

Abstract: Some cutaneous melanocytic lesions are notoriously difficult to diagnose by histopathology. For that reason, the Pathology Panel of the Dutch Melanoma Working Party was instituted and is regularly approached to provide an expert opinion on problem cases. In order to identify the most common diagnostic problems, 1069 consecutive referral cases of submitted lesions (1992 to 1994 inclusive) were analysed. About 60 per cent of the requests came from small laboratories, with up to three consultant pathologists. Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
47
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 5 publications
4
47
0
1
Order By: Relevance
“…The average discordance between reviewing pathologists was 19.4% in cases receiving an indeterminate score. The overall discordance of 14.1% observed in this study was higher than that for the cohort used in the previous validation study (4.7%) and similar to that reported by other investigations of disagreement in the histopathologic diagnosis of melanocytic lesions 3, 5…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The average discordance between reviewing pathologists was 19.4% in cases receiving an indeterminate score. The overall discordance of 14.1% observed in this study was higher than that for the cohort used in the previous validation study (4.7%) and similar to that reported by other investigations of disagreement in the histopathologic diagnosis of melanocytic lesions 3, 5…”
Section: Resultssupporting
confidence: 86%
“…For example, desmoplastic and nevoid melanomas were not specifically excluded from the cohort, but none of the cases classified as either of these 2 particular melanoma subtypes received a triple‐concordant diagnosis by histopathology. The high frequency of discordance among reviewing dermatopathologists in this study was similar to that observed in other assessments of clinical cohorts3, 4, 5, 6, 7 and highlights the need for adjunctive diagnostic tools. An evaluation of the gene signature against clinical outcomes would minimize cohort bias toward straightforward cases, and studies assessing test performance by comparison with clinical outcomes are currently underway.…”
Section: Discussionsupporting
confidence: 83%
“…The clearcut difference between the aberration patterns between nevi -no aberrations or presence of an isochromosome 11p -and melanoma -multiple chromosomal aberrations in over 95% of the casessuggests that chromosomal analyses may be of assistance in the classification of lesions that are ambiguous by histopathology. This aspect is of significant clinical relevance, because of the limitations of current techniques to classify reliably tumors that have overlapping histologic features (Farmer et al, 1996;Veenhuizen et al, 1997).…”
Section: Patterns Of Chromosomal Aberrations In Melanocytic Neoplasmsmentioning
confidence: 99%
“…It is interesting to note that in 8% of the cases the referring pathologist could not provide a confident diagnosis, in 14% the primary 'malignant' diagnosis had to be revised to 'benign' and in 17% the primary 'benign' diagnosis had to be revised to malignant. 7 Recently, genetic approaches have been reported to be of significant help for classifiying melanocytic tumors. Comparative genomic hybridizations (CGHs) demonstrated that specific chromosomal aberrations in melanoma were distinct from chromosomal alterations in nevi.…”
mentioning
confidence: 99%